Long-term outcome of therapist-guided internet-based cognitive behavioural therapy for body dysmorphic disorder (BDD-NET): a naturalistic 2-year follow-up after a randomised controlled trial. Issue 1 (15th January 2019) - Enander, Jesper; Ljótsson, Brjánn; Anderhell, Lina; Runeborg, Martin; Flygare, Oskar; Cottman, Oskar; Andersson, Erik; Dahlén, Sofia; Lichtenstein, Linn; Ivanov, Volen Z; Mataix-Cols, David; Rück, Christian
Abstract : Objectives: Most patients with body dysmorphic disorder (BDD) do not receive evidence-based treatment. A randomised controlled trial (RCT) has found that a therapist-guided internet-based cognitive–behavioural therapy (CBT) programme for BDD (BDD-NET) can be delivered safely via the internet with significant improvements in BDD symptom severity in the short term. The purpose of this study was to evaluate if the therapeutic gains of BDD-NET are maintained 2 years after treatment. Setting: Academic medical centre. Participants: A naturalistic 2-year follow-up study of the 88 self-referred adult outpatients with a diagnosis of BDD that had received BDD-NET within the context of the RCT. Primary and secondary outcomes: The primary outcome was the BDD-Yale-Brown Obsessive-Compulsive Scale (YBOCS). Responder status was defined as a ≥30% reduction in symptoms. Remission was defined as no longer meeting Diagnostic and Statistical Manual of Mental Disorders 5th edition criteria for BDD. Secondary outcomes included measures of depression, global functioning and quality of life. Results: The efficacy of BDD-NET was sustained long- term, with further improvements observed on the BDD-YBOCS during the follow-up period. At follow-up, 69% (95% CI 57% to 80%) were classified as responders and 56% (95% CI 43% to 69%) were in remission. Gains on depressive symptoms and global functioning were also sustained but not quality of life. A majority of participants reported that the main reason for seeking help for their BDD was the possibility to access the treatment from home. Conclusion: BDD-NET is an effective treatment for BDD, and the patients' gains are maintained in the long term. BDD-NET has the potential to increase access to CBT and may lower the threshold for BDD sufferers to seek help in the first place. Trial registration number: NCT02010619 .